In vitro study of solubilization ability of bovine pulp tissue using different irrigating solutions - Luiz Henrique Teixeira Fernandes; Kenner Bruno Miguita; Carlos Eduardo da Silveira Bueno; Alexandre Sigrist de Martin (Revista Sul-Brasileira de Odontologia, 2014)
The aim of this study was to evaluate in vitro the capacity of solubilization of bovine pulp tissue, promoted by the following auxiliary chemical solutions: 2.5% sodium hypochlorite at pH 9, 5.25 % sodium hypochlorite at pH 9, 2% chlorhexidine gel at pH 6, 17% EDTA at pH 7, and Smear-Clear®. Material and methods: A total of ten specimens of bovine pulp tissue, weighing 1.65 g each, were placed into flasks connected to a device developed for the study in order to reproduce irrigation dynamics. The flasks with the specimens received a volume of 80 ml of irrigating solution and the experimental times were 15, 30, 45 and 60 minutes. Results: The results were analyzed statistically by Kruskal-Wallis test to compare the different experiment times (15, 30, 45 and 60 minutes) of each irrigating solution. To compare the variation among the times of one solution, Kolmogorov-Smirlov test (Lilliefors) was used. Conclusion: Considering the results obtained and the limitations of the study, it can be concluded that 5.25% sodium hypochlorite exhibited the greatest solubilization ability, followed by 2.5% sodium hypochlorite, Smear-Clear®, 17% EDTA and 2% chlorhexidine gel.